1993
DOI: 10.1021/bi00071a012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sphingosine on peripheral membrane interactions: Comparison of adriamycin, cytochrome c, and phospholipase A2

Abstract: As revealed by resonance energy transfer utilizing pyrene-labeled phosphatidylcholine donor, the mainly electrostatically controlled binding of adriamycin (Adr) and cytochrome c (cyt c) to mixed egg yolk phosphatidic acid/phosphatidylcholine (eggPA/eggPC, 15:85 molar ratio) liposomes was reversed upon the inclusion of increasing contents of sphingosine. At a [sphingosine]/[eggPA] molar ratio of approximately 2:1, the degree of fluorescence quenching by cyt c and Adr was approximately the same as when using lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…4m–r; it did not affect LactC2 membrane localization, Supplementary Information, Fig. S2c)19,17. In contrast, sphingosine treatment allowed effective association of the DshKR/E mutant with Fz at the membrane, suggesting that the neutralization of surface charge rescues repulsion of the DshKR/E mutant from the membrane (Fig.…”
mentioning
confidence: 93%
“…4m–r; it did not affect LactC2 membrane localization, Supplementary Information, Fig. S2c)19,17. In contrast, sphingosine treatment allowed effective association of the DshKR/E mutant with Fz at the membrane, suggesting that the neutralization of surface charge rescues repulsion of the DshKR/E mutant from the membrane (Fig.…”
mentioning
confidence: 93%
“…Various studies suggest that the cellular functions of SPH are exerted more through its influence on the lipid phase behavior than its direct interaction with proteins [19,40,41]. The aim of our study was to examine the effect of SPH on domain morphology and its interactions with the raft-forming lipids, CHOL and SM.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noticing that electrostatics in biomembranes is, in general, dominated by the above negatively charged lipids. Yet, also cationic lipids are found, the most abundant being sphingosine [84] and studies with model membranes have shown its association with acidic phospholipids to regulate peripheral lipid–protein as well as lipid–small molecule interactions [85]. More detailed studies on model membranes have demonstrated the interplay of surface charge density and the dissociation behaviour of the acidic phospholipid headgroup to exert a pronounced impact on lipid–protein interactions evident as distinctly different binding modes of cytochrome c to protonated and deprotonated phospholipid [86, 87].…”
Section: Membrane Lipid Organizationmentioning
confidence: 99%